PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM KELAS XII DI MAN 1 KOTA MAKASSAR - Muhammad Nur Faisal Ridwan; Abdul Wahab; Muhammad Syahrul; Andi Bunyamin; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of student learning motivation in the subject of Islamic Cultural History, determine learning outcomes, and analyze the influence of learning motivation on the learning outcomes of class XII students at MAN 1 Makassar City. This study uses a quantitative approach with a correlational research type. The research population consisted of 386 12th-grade students, while the research sample consisted of 35 students. Data collection techniques were carried out through questionnaires and documentation, then analyzed using descriptive and inferential statistics with the help of SPSS. The results of the study show that the learning motivation of class XII students in the subject of Islamic Cultural History is in the high category with an average value of 78.40. Student learning outcomes are also in the good category with an average value of 82.15. The results of the analysis show that the data are normally distributed and have a linear relationship. Thus, learning motivation has a significant influence on the learning outcomes of class XII students in Islamic Cultural History at MAN 1 Makassar City. The higher the student's learning motivation, the better the learning outcomes obtained.